Role of cathepsin B in regulating migration and invasion of fibroblast-like synoviocytes into inflamed tissue from patients with rheumatoid arthritis. (24th July 2014) - Tong, B; Wan, B; Wei, Z; Wang, T; Zhao, P; Dou, Y; Lv, Z; Xia, Y; Dai, Y
Summary: Cathepsin B (CB), an important proteinase that participates in joint destruction in rheumatoid arthritis (RA), exhibits higher expression in fibroblast-like synoviocyte (FLS) of abnormal proliferative synovial tissues. Whether and how it affects the biological behaviours of RA-FLS, such as migration and invasion, are poorly understood. In the present study, CB expression in synovial tissues of patients with RA and ostearthritis (OA) were measured by quantitative polymerase chain reaction (qPCR) and immunohistochemistry (IHC), respectively. Stable depletion of endogenous CB was achieved by small interfering RNA (siRNA) transfection, and decrease of CB activity was acquired by using its specific inhibitor (CA074Me). The effects of CA074Me and RNA interference (RNAi) treatments on proliferation, migration, invasion, matrix metalloproteinase (MMP)-2/-9 expression, focal adhesion kinase (FAK) activation, and mitogen-activated protein kinases (MAPKs) phosphorylation of FLS were analysed. In RA synovial tissues, CB was expressed at elevated levels compared with OA synovial tissues. CA074Me could inhibit invasion of FLS obtained from RA patients in an ex-vivo invasion model. CA074Me and siRNA treatments suppressed the migration and invasion of FLS, reduced the activity, expression and mRNA level of MMP-2, restrained the activation of FAK and reduced the expression of F-actin. Moreover, CA074Me decreased the phosphorylation of P38 MAPK and c-Jun N-terminal kinase (JNK) in FLS, while siCB treatment reduced the phosphorylation of P38 but not JNK. CB substantially contributes to the invasive phenotype of FLS that leads to joint destruction in RA. This proteinase may show promise as a therapeutic target in inflammatory arthritis.